Development of low cost electrostatic spray - charging system for liquid formulations - DIPAK S. KHATAWKAR; Dr. Dhalin D (Guide) (Tavanur 2016 Department of Farm Power, Machinery and Energy)
to develop a low cost electrostatic nozzle and charging system compatible to a DC power source, study the dynamic charge acquisition, spray chargeability and depositional characteristics of the charged spray on plant targets of the developed system.
Development of low cost electrostatic spray - charging system for liquid formulations